THE EXISTENCE OF ENTOMOPATHOGENIC FUNGI ON RICE PLANTS RHIZOSPHERE - Noerfitryani, Noerfitryani; Hamzah, Hamzah (International Journal of Biosciences and Biotechnology; Vol 5 No 1 (2017), 2017)
Enthomophatogenic fungus is biological control. This research aimed to identify fungi on semi-organic and inorganic rice plants rhizosphere and proved as entomophatogenic fungi. This research was conducted in Biological control, Plant Pests and Diseases Department, Faculty of Agriculture, Universitas Hasanuddin, Makassar. Isolation of fungi with a modified insect bait method then tested in larvae, calculated mortality of larvae, Tenebrio molitor were infected by fungi were re-isolated and cultured in PDA media. The result showed that the average of T. molitor larvae mortality infected by enthomopathogenic fungi on semi-organic rhizosphere was around 24% and 8% on inorganic rhizosphere. The percentage mortality of larvae on semi-organic rhizosphere were infected by Fusarium sp. was around 20-60 %, Aspergillus sp. 60%-80% and Trichoderma sp. 80%, while in inorganic rhizosphere up to 100% were infected by Aspergillus spp.